2015
DOI: 10.1002/mde.2737
|View full text |Cite
|
Sign up to set email alerts
|

The Determinants of Price Adjustments in Retail Supermarkets

Abstract: This paper examines the determinants of price adjustment decisions by supermarkets to increase or decrease prices for 11 different food categories and evaluates the characteristics of these firms that influence these decisions. We use a unique dataset to analyze firm variables and industry variables and their impact on price adjustment in supermarket stores. The study contributes to the price adjustment literature by identifying determinants of price behavior by stores and product category. We find that the ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 72 publications
(93 reference statements)
1
10
0
Order By: Relevance
“…However, there is a disparity in the use of negotiated pricing as identified by Nagler et al (2015), Kenyon and Purcell (1999), Ajala and Adesehinwa (2007) and McEwan and Duffy (2000). The study also supports the findings by Volpe, Risch, and Boland (2015) and Jumah (2000) of the use of profit orientation in pork industries. However, it falls contrary to Buhr's (2004) findings of competitiveness objectives in pork industries.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…However, there is a disparity in the use of negotiated pricing as identified by Nagler et al (2015), Kenyon and Purcell (1999), Ajala and Adesehinwa (2007) and McEwan and Duffy (2000). The study also supports the findings by Volpe, Risch, and Boland (2015) and Jumah (2000) of the use of profit orientation in pork industries. However, it falls contrary to Buhr's (2004) findings of competitiveness objectives in pork industries.…”
Section: Discussionsupporting
confidence: 89%
“…Buhr (2004) found that pig industry organisations utilised competitive pricing objectives. However, Volpe, Risch, and Boland (2015) found that pork price increases and decreases were highly dependent on supplier prices and promotional prices, with least influence from competitor prices, indicating that pricing objectives were mainly swayed towards profit and sales orientation.…”
Section: Literature Review: Pricingmentioning
confidence: 91%
“…The negative consequences of competitors' price cuts come quickly into effect for the focal firm because they “work directly on purchase behavior […] rather than on cognitive processes preceding purchase” (Steenkamp et al, 2005, p. 38). Price cuts of competitors can lead to an erosion of market share and profitability of the focal firm (Chen & MacMillan, 1992; Smith, Ferrier, & Ndofor, 2001; Steenkamp et al, 2005; Upson, Ketchen, Connelly, & Ranft, 2012; Volpe, Risch, & Boland, 2017). They are especially threatening if other companies imitate this competitive action and thus start a price war (Rindova et al, 2004; Smith et al, 1991).…”
Section: Theoretical Background and Hypothesesmentioning
confidence: 99%
“…Second, this paper is based on store‐level analysis rather than product‐level analysis. Many researchers have studied dynamic pricing, changing the optimal price as demand varies, to analyze the retail industry, but they have merely taken into account the retailers' store level competition effect (Bitran & Caldentey, 2003; Elmaghraby & Keskinocak, 2003; Hamister & Suresh, 2008; Volpe & Cho, 2019; Volpe, Risch, & Boland, 2017). Previous marketing studies have employed the brand or product category as a level of analysis since each product line has a different demand pattern as well as a unique product life cycle (Nijs, Srinivasan, & Pauwels, 2007; Shankar & Bolton, 2004).…”
Section: Introductionmentioning
confidence: 99%